Peculiarities of competition in fitness sphere - Dobrokhotova E. V. (Innovative technologies in science and education, 2016)
the present article is devoted to examination of competetive interactions in fitness sphere. The author presents the ways of rivals counteraction in the analyzed sphere.
Keywords: конкуренция; бизнес; business; фитнес-индустрия; fitness-industry; сompetition